(untitled) (CIENCIA Y TECNOLOGÍA AGROPECUARIA, 2023)
Agribusinesses need to maximize the efficiency of resource use, and to do so, they have advanced tools to achieve organizational objectives such as agromanagement. The study aimed to analyze advanced agromanagement as a performance mechanism of Production Units. In this sense, it was based on a descriptive type of research with a non-experimental field design. On the other hand, the population was made up of fifty (50) subjects. In this sense, the information was collected through a questionnaire containing thirty-six (36), questions with alternatives on a Likert scale (S, Cs, Av, Cn and N), it was validated through the judgment process of experts. The results showed that inadequate use of agricultural resources is required, without defining an agricultural competitive process, to comply with the agricultural technical support needed by the human talent of the production units.